A Modular Reconfigurable Robot for Future Autonomous Extraterrestrial Missions - Alexey M. Romanov (IEEE, 2021)
This study proposes a heterogeneous modular reconfigurable robot called SABER (short for Step, Assembler, and Bridge Explorer Robot) that is suitable for future autonomous extraterrestrial missions. SABER comprises a platform and a reconfigurable rail and can operate in monowheel, rail trolley, and manipulator configurations. The monowheel configuration provides locomotion at a top speed of 10 km/h. The rail trolley configuration allows the robot to traverse gaps whose length is greater than its wheel diameter, climb steps whose height is no taller than the wheel radius, and pass through passages narrower than the wheel diameter. The manipulator configuration enables the robot to manipulate objects using two robotic arms with changeable tools. This design allows several SABERs to work as a team to enlarge their working area or enhance their mechanical capabilities. As such, SABERs can undertake various tasks in extraterrestrial missions, including exploration, outpost building and equipment maintenance. The key feature of the SABER is its mechanical transmission that allows its platform to move rapidly along a rail made from the manipulators of the robot. We also formulated the novel concept of a jamming safety diagram that is used to determine controller precision requirements to prevent the transmission from jamming. Finally, a new positioning controller meeting those requirements was introduced and implemented as field-programmable-gate-array firmware that is compatible with a wide range of low-cost integrated circuits. In numerical simulations, we evaluated SABER with respect to its speed, acceleration, oscillation, and ability to negotiate gaps and steps; SABER performed as well as or better than existing autonomous mobile robots and modular reconfigurable robots.